Exploring German Language Skills Learning Experiences Using The NURS Teaching Model - Nurming Saleh; Muhammad Nur Ashar Asnur; Sein U Swe (International Journal of Language Education, 2023)
This mixed-method research study explores German skills using the NURS teaching model for students. It was conducted in the German educational department program at the Faculty of Language and Literature at Makassar State University. The research subject was 28 German academic students from two classes in the second semester. Research instruments in this study include syllabi, teaching plans, student activity sheets, and formative tests. Researchers use reading, listening, writing, and speaking tests to determine students’ competencies and skills. The data was examined by researchers using percentage techniques. German Average score of the students before they learn using the NURS teaching model is 75. The result shows that the average student's German-language skills in the A class are 80.75 and 83.50 for the B class. These improvements could be seen in the improvement in each class. Students of A class have improved in listening, 7.5% in reading, 13% in writing, and 11.5% in speaking. Conversely, students of B class have improved by 12% in listening, 9% in reading, 18% in writing and 15% in speaking. Another value of using the NURS teaching model in learning German is that it positively effect on the teachers’ skills, like management of teaching, time, and how to make students more enthusiastic during the learning process. It can be concluded that the NURS teaching model can improve students' German skills in the German educational department at the Faculty of Language and Literature of Makassar State University.